PENGARUH STUNTING SMART CHATTING TERHADAP PENGETAHUAN DAN SIKAP IBU DENGAN BALITA DI DESA PERING KECAMATAN BLAHBATUH KABUPATEN GIANYAR - I Gede Bayu Permana Waisnawa; Made Rini Damayanti; Ida Arimurti Sanjiwani (Coping: Community of Publishing in Nursing, 2021)
Improving knowledge and attitudes about stunting among mother with toddler through health education can play an important role as an effort to decrease the incidence of stunting. Stunting Smart Chatting is one of mHealth media that can be used in the process of providing health education. This study aimed to determine the effect of Stunting Smart Chatting on knowledge and attitudes about stunting among mothers in Pering Village, Blahbatuh District, Gianyar Regency. This study was a quasi-experimental with a pretest-posttest one group design. Samples were selected using simple random sampling and were given messages through WhatsApp-based short messages sent three times a week for three weeks duration. Paired t-test and Wilcoxon test were used in this study. Statistical tests indicated that there were differences in knowledge (p=0,001) and attitude (p<0,001) before and after the intervention. Based on these results, it can be concluded that Stunting Smart Chatting can improve the knowledge and attitudes about stunting among mothers with toddlers in Pering Village, Blahbatuh District, Gianyar Regency. The Stunting Smart Chatting as a health education media is recommended to be used in a community setting.